STRUCTURAL-ALGORITHMIC MEAN OF THE AUTOMATED PLANNING OF CALCULABLE MODELS - Gorbatyuk, Anatoliy; Gorbatyuk, Sergey (International Journal of Computing, 2014)
The present paper is devoted to the scientific and technical solution of an actual problem of developing models and methods of the structural-algorithmic organization of parallel computing processes for enhancement of efficiency of computer systems. The method of algostructural designing of computing models has been proposed. It performs automated design of model by using library algostructures and connections among them. The algostructural models reconstruction method which provides structuring on the base of equal transformations has been improved. The calculation paralleling method in algostructures has been developed. It accounts for structure-algorithmic organization of the models and provides a calculation optimization and allows a calculation time to be decreased, available technological resources to be effectively used. The method of structural reconfiguration in problem-oriented algostructural construction is in progress development. The automated design technology of algostructural models is in progress development. The proposed technology provides effective designing of computing models.